Adolescents’ Identity Formation as Learners in Sukma Bangsa School Pidie, Aceh, Indonesia - Nurhayati, Nurhayati; Dewi, Ratna Sari; Ropo, Eero; Räihä, Pekka (Sukma: Jurnal Pendidikan, 2017)
This study aimed to explore how adolescents performed towards their identity as learners in Sukma Bangsa School Pidie (SBP) through a phenomenographic approach. More specifically, the research had purpose to understand the way adolescents construct their learning identity in a school environment. The findings suggested that there were variations in the way adolescents experienced their learning identity that might encourage them to achieve different degrees of motivation, self-perceptions (self-efficacy, self-concept, and self-esteem), autonomy, and self-development towards their identity as learners. In this study, students exhibited a high level of self-efficacy and self-development, an average level of self-esteem and autonomy, and close to an average level of self-concept and motivation in constructing their identity as learners. The students also revealed that the highest accomplishment of their experiences was in showing their confidence towards learning attitude, whereas the lowest one was in adult attachment. Adult attachment therefore is pivotal to moderate students who have either low willingness to study or low self-conception.[Penelitian ini bertujuan untuk mengeksplorasi pembentukan identitas remaja sebagai peserta didik di Sekolah Sukma Bangsa Pidie (SBP) melalui pendekatan fenomenografi. Lebih khusus lagi, penelitian ini bertujuan untuk memahami bagaimana remaja membangun identitas pembelajaran mereka di lingkungan sekolah. Temuan menunjukkan adanya variasi cara remaja membentuk identitas mereka, yang mendorong mereka mencapai tingkat motivasi, persepsi diri (self-efficacy, self-concept, dan self esteem), otonomi, dan pengembangan diri yang berbeda. Dalam penelitian ini, siswa menunjukkan tingkat self-efficacy dan self-development yang tinggi, tingkat self-esteem dan otonomi yang rata-rata serta konsep diri dan motivasi mendekati tingkat rata-rata. Pengalaman siswa yang paling tinggi menunjukkan kepercayaan diri terhadap sikap belajar, sedangkan yang terendah menunjukkan keterikatan pada orang dewasa. Oleh karena itu, keterikatan pada orang dewasa sangat penting bagi siswa yang memiliki kesediaan untuk belajar atau konsepsi diri rendah.]